Gastrointestinal endoscopy infection control strategy during COVID‐19 pandemic: Experience from a tertiary medical center in China. Issue 4 (24th August 2020) - Zhang, Shengyu; Wu, Xi; Pan, Hui; Wu, Dong; Xu, Tao; Shen, Ning; Zhang, Yizhen; Feng, Yunlu; Wang, Qiang; Jiang, Qingwei; Guo, Tao; Wu, Dongsheng; et al.
Abstract : Objectives: Coronavirus disease 2019 (COVID‐19) has spread globally and become a pandemic. The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) not only infects the gastrointestinal (GI) tract and causes GI symptoms, but also increases nosocomial transmission risk during endoscopic procedures for aerosol generation. We hereby share our infection control strategies aiming to minimize COVID‐19 transmission in the endoscopy center. Methods: We established our infection control strategies based on the guidance of Chinese Society of Digestive Endoscopy and inputs from hospital infection control experts: admission control through the procedure and patient triage, environmental control to reduce possible virus exposure, proper usage of personal protective equipment (PPE), and scope disinfection and room decontamination. All endoscopic procedures accomplished during COVID‐19 outbreak and progress of stepwise resumption of elective endoscopy procedures were retrospectively reviewed. Results: Only urgent or semi‐urgent procedures were performed during COVID‐19 outbreak. After no local new‐onset COVID‐19 case in Beijing for four weeks, we reopened the endoscopy center for elective procedures and monitored the outbreak continuously while maintaining a sustainable endoscopy service. Conclusions: It is imperative that all endoscopy centers should establish standard infection control strategies in order to fight COVID‐19 pandemic based on national guidance and academic society guidelines and tailor them to individual resources. These measures and setup can also be reserved for future pandemics.